Effects of neutron on reverse bias characteristics of commercially available SI and gaas diodes - Che Omar, Nuurul Iffah; Alang Md Rashid, Nahrul Khair; Abdul Karim, Julia; Abdullah , Jaafar; Hasbullah, Nurul Fadzlin (INSI Publications, 2012)
This study investigates the effects of neutron radiation on reverse bias characteristics of commercial silicon and gallium arsenide diodes. Reverse bias current-voltage and capacitance-voltage characteristics of the diodes were measured at room temperature before and after irradiation. The diodes were irradiated using Pneumatic Transfer System facility at PUSPATI TRIGA reactor with neutron fluences up to (6.038  3.067) x1012 n /cm2.s for a period of 1, 3 and 5 minutes. The results showed an increase in leakage current for all diodes which may be due to the existence of neutron-induced displacement defects introduced into the semiconductor lattice. The doping concentration of gallium arsenide diodes is observed to decrease after irradiation which is attributed to carrier removal process.